Establishment of an efficient regeneration and Agrobacterium transformation system in mature embryos of calla lily (Zantedeschia spp.) - Sun, Xuan; Wang, Yi; Yang, Tuo; Wang, Xue; Wang, Huanxiao; Wang, Di; Liu, Hongyan; Wang, Xian; Zhang, Guojun; Wei, Zunzheng (Frontiers in Genetics, 2022)
Calla lily (Zantedeschia spp.) have great aesthetic value due to their spathe-like appearance and richness of coloration. However, embryonic callus regeneration is absent from its current regeneration mechanism. As a result, the construction of an effective and stable genetic transformation system is hampered, which severely hinders breeding efforts. In this research, the callus induction effectiveness of calla lily seed embryos of various maturities was evaluated, and the findings indicated that mature seed embryos were more suitable for in vitro regeneration. Using orthogonal design experiments, the primary elements influencing in vitro regeneration, such as plant growth regulators, genotypes, and nanoscale materials, which was emergent uses in vitro regeneration, were investigated. The findings indicated that MS supplemented with 6-BA 2 mg/L and NAA 0.1 mg/L was the optimal medium for callus induction; the regeneration medium was MS supplemented with 6-BA 2 mg/L NAA 0.2 mg/L and 1 mg/L CNTs; and the rooting medium was MS supplemented with 6-BA 2 mg/L NAA 0.7 mg/L and 2 mg/L CNTs. This allowed us to verify, in principle, that the Agrobacterium tumefaciens-mediated genetic transformation system operates under optimal circumstances using the GUS reporter gene. Here, we developed a seed embryo-based genetic transformation regeneration system, which set the stage for future attempts to develop new varieties of calla lily.